Advancing equity and diversity in student affairs : a festschrift in honor of Melvin C. Terrell - Terrell, Melvin C.; Jackson, Jerlando F. L.; Charlteston, LaVar J.; Gilbert, Cornelius (Contemporary perspectives on access, equity, and achievement., 2017)
This Festschrift has a dual purpose: (a) highlight how student affairs has grown as a field of practice in response to the growth of student diversity on college campuses, and (b) honor the remarkable career of Melvin C. Terrell. As one of the unique contributions to higher education attributed to the United States, the practice of student affairs has played a significant role in supporting students as access to college has broadened. In turn, key principles of practice had to evolve to appropriately take into consideration diverse student development theory and needs. The span of Melvin C. Terrell's legendary accomplishments neatly aligned with the professional evolution of student affairs. Each of the chapters in this Festschrift artfully straddle the dual purpose of this volume. Researchers, practitioners, and key decision-makers will equally be empowered to employ the lessons and approaches informed by the evolution of student affairs over the past 30 years. - Presents cutting edge and thought-provoking chapters on the evolution of student affairs practice shaped by the diversification of the student body and practitioners - Contributions from some of the best minds and practitioners in the field - Includes curated chapters that capture advancements in student affairs practice informed by equity and diversity, while honoring the unique contribution of Melvin C. Terrell to the field.